Factors Affecting Teachers'Implementation Of Communicative Language Curriculum In Bangladesh - Rahman, Mohammad Mosiur (2018)
This study focuses on the selected factors affecting teachers’ implementation of the NCTB’s Communicative Language Teaching (CLT) curriculum in secondary schools in Bangladesh. The study aims to reveal the factors that challenge teachers’ implementation of CLT in the English classrooms in secondary level. The study is qualitative in nature and adopted phenomenology approach to explore how teachers experience the phenomenon. Four schools were chosen from Dhaka, the capital of the country. Eight (8) participants were chosen from urban schools. Semi structured interview, observation and document analysis of curriculum, assessment, and teaching materials were the instrument of data collection.